Immunological Aspects of X-Linked Chronic Granulomatous Disease Female Carriers - Maria Chiriaco; Irene Salfa; Giorgiana Madalina Ursu; Cristina Cifaldi; Silvia Di Cesare; Paolo Rossi; Gigliola Di Matteo; Andrea Finocchi (MDPI AG, 2021)
X-linked Granulomatous Disease (XL-CGD) carriers were previously thought to be clinically healthy because random X-chromosome inactivation (XCI) allows approximately half of their phagocytes/monocytes to express functional gp91phox protein. This supports the NADPH oxidase activity necessary for the killing of engulfed pathogens. Some XL-CGD carriers suffer from inflammatory and autoimmune manifestations as well as infections, although the skewed-XCI of a mutated allele is reported to be exclusively determinant for infection susceptibility. Indeed, immune dysregulation could be determined by dysfunctional non-phagocytic leukocytes rather than the percentage of functioning neutrophils. Here we investigated in a cohort of 12 X-CGD female carriers at a particular time of their life the gp91phox protein expression/function and how this affects immune cell function. We showed that 50% of carriers have an age-independent skewed-XCI and 65% of them have a misrepresented expression of the wild-type gene. The majority of carriers manifested immune dysregulation and GI manifestations regardless of age and XCI. Immunological investigations revealed an increase in CD19+ B cells, CD56bright-NK cell percentage, a slightly altered CD107a upregulation on CD4+ T cells, and reduced INFγ-production by CD4+ and CD8+ cells. Notably, we demonstrated that the residual level of ROS robustly correlates with INFγ-expressing T cells, suggesting a role in promoting immune dysregulation in carriers.